Homeotic genes and the arthropod head: Expression patterns of the labial, proboscipedia, and Deformed genes in crustaceans and insects - Abzhanov, Arhat (The National Academy of Sciences, 1999)
cDNA fragments of the homologues of the Drosophila head homeotic genes labial (lab), proboscipedia (pb), and Deformed (Dfd) have been isolated from the crustacean Porcellio scaber. Because the accumulation domains of the head homeotic complex (Hox) genes had not been previously reported for crustaceans, we studied the expression patterns of these genes in P. scaber embryos by using in situ hybridization. The P. scaber lab homologue is expressed in the developing second antennal segment and its appendages. This expression domain in crustaceans and in the homologous intercalary segment of insects suggests that the lab gene specified this metamere in the last common ancestor of these two groups. The expression domain of the P. scaber pb gene is in the posterior part of the second antennal segment. This domain, in contrast to that in insects, is colinear with the domains of other head genes in P. scaber, and it differs from the insect pb gene expression domain in the posterior mouthparts, suggesting that the insect and crustacean patterns evolved independently from a broader ancestral domain similar to that found in modern chelicerates. P. scaber Dfd is expressed in the mandibular segment and paragnaths (a pair of ventral mouthpart structures associated with the stomodeum) and differs from insects, where expression is in the mandibular and maxillary segments. Thus, like pb, Dfd shows a divergent Hox gene deployment. We conclude that homologous structures of the mandibulate head display striking differences in their underlying developmental programs related to Hox gene expression.